The Positive Impact of Leadership and Work Motivation on Job Satisfaction of Honorary School Administration Staff - Apriliyani, Wina Dwi; Karnati, Neti; Sugiarto, Sugiarto; Ifnuari, Moh. Reza (Journal of Education Reseach and Evaluation, 2022)
In order to improve the quality of performance of administrative staff in schools, efforts are always made to increase job satisfaction. The increase in job satisfaction of administrative staff is influenced by many factors, including the principal's leadership role as a direct supervisor and the motivation of administrative staff. This study was conducted to analyse the influence of leadership and motivation on honorary school administration staff. The time used during research activities is planned for nine months. The data analysis used is structural equation model (SEM) using AMOS software. The findings from the study that there is a principal’s leadership style have a positive and significant effect on the job satisfaction of honorary school administrative staff. The ability of the principal's management to contribute significantly to the service of administrative staff and high work motivation will have a positive effect on job satisfaction. As honorary school administrators who play an essential role in an educational institution, they must have the awareness to motivate themselves in carrying out their duties so that the desired goals can be achieved.